Genomic analysis of SARS-CoV-2 variants of concern identified from the ChAdOx1 nCoV-19 immunized patients from southwest part of Bangladesh - Al-Emran, Hassan M.; Hasan, Md. Shazid; Setu, Md. Ali Ahasan; Rahman, M. Shaminur; Ul Alam, Rubayet A. S. M.; Sarkar, Shovon Lal; Islam, Md. Tanvir; Islam, Mir Raihanul; Rahman, Mohammad Mahfuzur; Islam, Ovinu Kibria; Jahid, Iqbal Kabir; Hossain, M. Anwar (Elsevier, 2022)
Background Bangladesh introduced ChAdOx1 nCoV-19 since February, 2021 and in six months, only a small population (12.8%) received either one or two dose of vaccination like other low-income countries. The COVID-19 infections were continued to roll all over the places although the information on genomic variations of SARS-CoV-2 between both immunized and unimmunized group was unavailable. The objective of this study was to compare the proportion of immune escaping variants between those groups. Methods A total of 4718 nasopharygeal samples were collected from March 1 until April 15, 2021, of which, 834 (18%) were SARS-CoV-2 positive. The minimum sample size was calculated as 108 who were randomly selected for telephone interview and provided consent. The prevalence of SARS-CoV-2 variants and disease severity among both immunized and unimmunized groups was measured. A total of 63 spike protein sequences and 14 whole-genome sequences were performed from both groups and phylogenetic reconstruction and mutation analysis were compared. Results A total of 40 respondents (37%, N = 108) received single-dose and 2 (2%) received both doses of ChAdOx1 nCoV-19 vaccine, which significantly reduce dry cough, loss of appetite and difficulties in breathing compared to none. There was no significant difference in hospitalization, duration of hospitalization or reduction of other symptoms like running nose, muscle pain, shortness of breathing or generalized weakness between immunized and unimmunized groups. Spike protein sequence assumed 21 (87.5%) B.1.351, one B.1.526 and two 20B variants in immunized group compared to 27 (69%) B.1.351, 5 (13%) B.1.1.7, 4 (10%) 20B, 2 B.1.526 and one B.1.427 variant in unimmunized group. Whole genome sequence analysis of 14 cases identified seven B.1.351 Beta V2, three B.1.1.7 Alpha V1, one B.1.526 Eta and the rest three 20B variants. Conclusion Our study observed that ChAdOx1 could not prevent the new infection or severe COVID-19 disease outcome with single dose while the infections were mostly caused by B.1.351 variants in Bangladesh.